Faculty peer coaching in higher education : opportunities, explorations, and research from the field - Rainville, Kristin N.; Title, David G.; Desrochers, Cynthia G. (Transforming teaching and learning in higher education., 2023)
Peer Coaching is a collaborative, reciprocal practice where faculty members observe, reflect, and improve their instructional practices with the goal of improved learning for all students. This edited book includes chapters describing faculty peer coaching initiatives in universities world-wide. Section one includes chapters that give an overview of what faculty peer coaching is and what the benefits of faculty peer coaching can be. The second section of the book explores the theoretical and practical implications of engaging in faculty peer coaching and the trust and vulnerability that comes along with opening up your instructional practices to a colleague. Section three of the book includes several examples of peer coaching initiatives across various disciplines in higher education settings. Section four situates peer coaching in the broader institutional framework. This book is a must for leaders of faculty development initiatives, directors and staff from teaching & learning centers, department chairs, faculty, graduate students, deans, student services staff, chief academic officers, and educational consultants.